The historical racial regime and racial inequality in poverty in the American South - Regina S. Baker (Luxembourg Income Study (LIS), 2021)
Building on literatures on racial regimes and the legacy of slavery, this study conceptualizes and constructs a novel measure of the historical racial regime (HRR), and examines how HRR influences contemporary poverty and racial inequality in the American South. The HRR scale measures different manifestations of the U.S. racial regime across different historical periods (i.e. slavery and Jim Crow) and is based on state-level institutions including slavery, sharecropping, disfranchisement, and segregation. Using Current Population Study data from the Luxembourg Income Study 2010-2018 for 527,829 Southerners and historical state-level data from various sources, evidence is triangulated from bivariate associations, multilevel regressions, and decomposition analyses. Results show that residing in a state with stronger HRR is not significantly associated with greater poverty for all and especially not among White Southerners. Rather, a higher level of HRR worsens Black poverty and especially Black-White inequalities in poverty. Further, HRR explains a significant share of the Black-White poverty gap. These results hold even after adjusting for a wide variety of individual-level variables, many of which plausibly mediate the influence of HRR. Altogether, this study demonstrates the enduring influence of historical state institutions on contemporary poverty and inequality.
Keywords: 330; Armut; Einkommensverteilung; Ethnische Diskriminierung; Schwarze Menschen; USA (Südstaaten); USA